Evil Eye Belief In Turkish Culture: Myth Of Evil Eye Bead - Tuncer Manzakoğlu, Bilgen; Türkmenoğlu Berkan, Saliha (The Turkish Online Journal of Design Art and Communication, 2016)
Evil eye belief is found in many parts of the world and it plays a major social role in a large number of cultural contexts. The history of evil eye bead usage dated back to ancient times, but upon time it’s meaning have been re-constructed by culture. This paper focused on an amulet based commodity “evil eye bead” used against evil eye and for ornament in Turkey. In order to analyze the myth of evil eye bead, two-sectioned survey was conducted. First section determined evil eye belief rate, participant profile and objects against evil eye. In the second section, the semantic dimensions of evil eye bead was analyzed in the myth level encompassing its perception and function as a cultural opponent act. This paper interrogated the role of culture, geography, and history on the evil eye bead myth.
Keywords: Evil Eye Bead; Culture; Myth; Semiology